Investigating Reading Motivation in Indonesian and English among EFL Students - Fahmi, Arfan (Proceeding of International Conference on Teacher Training and Education, 2016)
Closely looking at reading motivation in L1 and L2 can lighten English teacher and educator toreformulate their approaches and strategies in giving reading instruction. In response to this, the studyintends to adapt and validate an eight reading motivational dimensions (Lin et al 2012) and one addeddimension; self-confidence for both Indonesian as an L1 and EFL as an L2 using confirmatory factoranalyses, and compare motivations for reading Indonesian and reading English across all nine categoriesusing descriptive statistics and correlation. Attempting to reach the objectives, eighty three second yearnon-English major complete a questionnaire on nine separate motivational subscales related to readingIndonesian and English behavior. Motivation in this study covers self-efficacy, curiosity, involvement,recreation, social-peer attitudes, school grades, instrumentalism, self-confidence and social-familyattitudes. The result concerning with the Instrument validation are all factor loadings in the adaptedMRQ` are significantly different from 0 at p .001, reliabilities were greater than .70 indicatedreasonably good internal consistency, and all motivational dimensions for English and most motivationaldimensions for Indonesian were above or closely approaching .70.The results show that studentsâ Selfefficacy, curiosity, involvement, recreation, and social peer are significantly higher in Indonesian than inEnglish. Grade motivation variable does not differ for the two languages. Whereas, instrumentalism,social family, and self-confidence are significantly higher in English than in Indonesian. Theimplications of these findings are discussed in respect to the approaches and strategies of readinginstructional program.